"You keep telling me what has been lost, and I keep telling you something remains." A personal response to: Scar Tissue by Michael Ignatieff. Issue 2 (1st December 2002) - Lewis, W
Abstract : Michael Ignatieff is well known as a journalist and broadcaster of a distinctly intellectual kind. He has written movingly on the trauma of modern warfare and Europe following the Cold War. His CV also boasts of studies on the Scottish Enlightenment and nineteenth century penal policy. Additionally, his Booker short listed novel Scar Tissue is one of the most interesting studies of medicine and the human consequences of disease of the last decade.